Seismisitas di Wilayah Jawa Tengah dan Sekitarnya Berdasarkan Hasil Relokasi Hiposenter dari Empat Jaringan Seismik Menggunakan Model Kecepatan 3-D - Ramdhan, Mohamad; Priyobudi; Kristyawan, Said; Sembiring, Andry Syaly (BRIN Publishing, 2020)
Hypocenter relocation is a method used to get precise earthquake parameters. They will be useful for an advanced tectonic study like seismic hazard assessment in an area. The hypocenter relocation using a 3-D velocity model will theoretically obtain better results than a 1-D velocity model because the earth subsurface model is closed with a 3-D model. Some 767 earthquakes recorded by DOMERAPI, MERAMEX, BMKG, and BPPTKG networks used in this research. They were relocated by using a 3-D velocity model and analyzed for seismotectonic study in Central Java area and its surroundings. The result of hypocenter relocation using a 3-D velocity model is successfully detecting some tectonic features more clearly like columnar structure related to the backthrust structure at the south of Kebumen. The west-east vertical cross-section crossing the Opak fault indicates the dip of the fault plane is directing to the east. This study could not identify the double seismic zone, which was detected by the previous research. Some volcano-tectonic (VT) earthquakes related to the shallow magma activity of Mount Merapi also are detected clearly in this study.